The art of memory : an ethnographer's journey - Varese, Stefano (History and social sciences series., 2020)
"Combining personal and family recollections with incisive accounts of academic, political, and institutional experiences, The Art of Memory offers a remarkable account of the life of one of the foremost Latin American ethnographers and a leading expert in Indigenous cultures, peoples, and cosmologies. Varese narrates the story of his journey from Italy to Peru, his formative years as an anthropologist and the critical work he did with Amazonian communities in the 1970s, his transformation into an activist scholar, his move to Mexico and his long-standing commitment with the peoples of Oaxaca, and his life as an academic in the United States ... combines the personal, the political, and the transnational to produce a vivid account of a unique and fulfilling journey"--